Pembaharuan Hukum Kontrak sebagai Antisipasi Transaksi Electronic Commerce - Ridwan Khairandy (Fakultas Hukum Universitas Islam Indonesia, 2001)
The following article examines the possible reformation of the contract law Inrelation to the rising use of online contract in commercial business activities. It'sgenerally recognizedthat the conventional contract law has been unable to over come various legal problems stemming from on line contract. There are three ways to reform such a contract law, namely:(1) through legislation by adopting some existing model sof law; (2) through the establishment of customary law like lexmer catoria; (3) through cases law. Though the arrangement through legislation is do nepartially, but the substance mustbe integrative so that It can run to ward a cyberspace.